Effects of mexiletine on hyperexcitability in sporadic amyotrophic lateral sclerosis: Preliminary findings from a small phase II randomized controlled trial. Issue 3 (31st December 2020) - Weiss, Michael D.; Macklin, Eric A.; McIlduff, Courtney E.; Vucic, Steve; Wainger, Brian J.; Kiernan, Matthew C.; Goutman, Stephen A.; Goyal, Namita A.; Rutkove, Seward B.; Ladha, Shafeeq S.; Chen, I‐Hweii Amy; Harms, Matthew B.; et al.
Abstract: Background: To collect preliminary data on the effects of mexiletine on cortical and axonal hyperexcitability in sporadic amyotrophic lateral sclerosis (ALS) in a phase 2 double‐blind randomized controlled trial. Methods: Twenty ALS subjects were randomized to placebo and mexiletine 300 or 600 mg daily for 4 wk and assessed by transcranial magnetic stimulation and axonal excitability studies. The primary endpoint was change in resting motor threshold (RMT). Results: RMT was unchanged with 4 wk of mexiletine (combined active therapies) as compared to placebo, which showed a significant increase ( P = .039). Reductions of motor evoked potential (MEP) amplitude ( P = .013) and accommodation half‐time ( P = .002), secondary outcome measures of cortical and axonal excitability, respectively, were also evident at 4 wk on mexiletine. Conclusions: The relative stabilization of RMT in the treated subjects was unexpected and could be attributed to unaccounted sources of error or chance. However, a possible alternative cause is neuromodulation preventing an increase. The change in MEP amplitude and accommodation half‐time supports the reduction of cortical and axonal hyperexcitability with mexiletine.